Oligomerization and Conformational Change Turn Monomeric β-Amyloid and Tau Proteins Toxic: Their Role in Alzheimer’s Pathogenesis - Penke, Botond (Molecules, 2020)
The structural polymorphism and the physiological and pathophysiological roles of two important proteins, β-amyloid (Aβ) and tau, that play a key role in Alzheimer’s disease (AD) are reviewed. Recent results demonstrate that monomeric Aβ has important physiological functions. Toxic oligomeric Aβ assemblies (AβOs) may play a decisive role in AD pathogenesis. The polymorph fibrillar Aβ (fAβ) form has a very ordered cross-β structure and is assumed to be non-toxic. Tau monomers also have several important physiological actions; however, their oligomerization leads to toxic oligomers (TauOs). Further polymerization results in probably non-toxic fibrillar structures, among others neurofibrillary tangles (NFTs). Their structure was determined by cryo-electron microscopy at atomic level. Both AβOs and TauOs may initiate neurodegenerative processes, and their interactions and crosstalk determine the pathophysiological changes in AD. TauOs (perhaps also AβO) have prionoid character, and they may be responsible for cell-to-cell spreading of the disease. Both extra- and intracellular AβOs and TauOs (and not the previously hypothesized amyloid plaques and NFTs) may represent the novel targets of AD drug research.